Correlation of fluoride intake with haemoglobin level and intelligence quotient in 8–12 year aged children: an observational study from India - Ruchi Singhal; Ritu Namdev; Adarsh Kumar; Amrish Bhagol; Supriya S. (BMC Public Health)
Abstract Background Fluorosis caused by excess intake of fluoride can affects various soft tissues of the body, such as the gastrointestinal tract, blood, brain tissues and thyroid gland apart from dental fluorosis and skeletal fluorosis. Nonskeletal fluorosis is considered reversible if diagnosed early and treated promptly. Therefore, diagnostic methods that can be easily performed even by primary health care workers and depict any ongoing health problems, should be validated. Dental fluorosis, assessment of fluoride in urine and water are tests that fulfill these requirements. To date, no study has correlated haemoglobin (Hb) with dental fluorosis; moreover, studies focusing on intelligence quotient (IQ) had conflicting results and need further research. Hence, study was conducted to determine any relationship among different fluoride assessment parameters (severity of dental fluorosis, fluoride level in urine and drinking water) with IQ status and hemoglobin level of children aged 8–12 years, affected with or without dental fluorosis. Methods A total of 300 children aged 8–12 years were evaluated for dental fluorosis via Dean’s index, IQ level via Raven’s coloured progressive matrices test, Hb level, and fluoride content in water and urine. Results Water fluoride, age and gender were significantly associated with Hb. Intelligence was significantly related to urinary fluoride levels. Presence or absence of dental fluorosis and its severity were not significantly related to IQ or Hb. Conclusions Excess fluoride intake has adverse effects on hematological parameters and children’s cognitive neurodevelopment, which were evaluated by current fluoride exposure markers, i.e., water and urinary fluoride. However, dental fluorosis cannot be used as a definitive assessment marker for these conditions, as it is not significantly correlated with these conditions.